2016
DOI: 10.1117/12.2227754
|View full text |Cite
|
Sign up to set email alerts
|

Recent progress in plasmonic colour filters for image sensor and multispectral applications

Abstract: Using nanostructured thin metal films as colour filters offers several important advantages, in particular high tunability across the entire visible spectrum and some of the infrared region, and also compatibility with conventional CMOS processes. Since 2003, the field of plasmonic colour filters has evolved rapidly and several different designs and materials, or combination of materials, have been proposed and studied. In this paper we present a simulation study for a singlestep lithographically patterned mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 12 publications
(10 reference statements)
0
11
0
Order By: Relevance
“…Moreover, the addition of a second top thin metallic layer in the MIM structure (from configuration (iii) to (ii)) greatly reduces the transmission efficiency of the second broad peak at longer wavelengths -which is almost of the same magnitude as the first narrower resonance in configuration (iii) -and strongly compromises the passband characteristics of the filter, causing optical colour cross-talk in particular between the blue and red part of the visible spectrum. 31 Previous studies 10,32 have demonstrated that when the propagation constant of SPPs, k SPP , (Equation (1)) matches the reciprocal vectors G ij given by the periodicity of the array (Equation (2)) minima in transmission appear, ascribed to the spectral location of Wood-Rayleigh anomalies. The transmission maxima, or EOT peaks, appear then red-shifted in wavelength.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the addition of a second top thin metallic layer in the MIM structure (from configuration (iii) to (ii)) greatly reduces the transmission efficiency of the second broad peak at longer wavelengths -which is almost of the same magnitude as the first narrower resonance in configuration (iii) -and strongly compromises the passband characteristics of the filter, causing optical colour cross-talk in particular between the blue and red part of the visible spectrum. 31 Previous studies 10,32 have demonstrated that when the propagation constant of SPPs, k SPP , (Equation (1)) matches the reciprocal vectors G ij given by the periodicity of the array (Equation (2)) minima in transmission appear, ascribed to the spectral location of Wood-Rayleigh anomalies. The transmission maxima, or EOT peaks, appear then red-shifted in wavelength.…”
Section: Resultsmentioning
confidence: 99%
“…Figure a presents the schematic top view (i) and cross-section (ii) of the proposed MIM architecture, in comparison with the cross sections (iii) and (iv) , of two previously reported configurations based on periodic hexagonal nanohole arrays. Their transmission characteristics have been simulated (see Methods for details) and the results are presented in Figure b.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hole array periodicity is varied to tune the SP resonance wavelength causing spectral shifts in the corresponding spectral curves. Recently, plasmonic lters composed of periodic microhole arrays in noble metals like gold (Au), and silver (Ag) are demonstrated by exploiting SSP resonance [21][22][23]. Jang et al further demonstrated spectral imaging with a square array of micron-sized holes in Au lm on gallium arsenide dielectric as an SSP structure [24].…”
Section: Introductionmentioning
confidence: 99%
“…These filters manipulate light in a promising way to create imaging technologies with accurate color representation. While nanostructured plasmonic hole arrays have been widely used as color filters in CMOS image sensors operating within the visible range of 400-700 nm [12][13][14][15], a fully-functional thermal multispectral camera with plasmonic hole array has not yet been reported to the best of our knowledge. Such next-generation thermal imaging sensors could have significant implications in the fields of multispectral imaging and spectroscopy with a wide range of applications such as surveillance, medical imaging, and non-destructive investigation.…”
Section: Introductionmentioning
confidence: 99%